SOLVING PARTIAL DIFFERENTIAL EQUATIONS IN MATLAB - Rathour, Laxmi; Obradovic, Dragan; Narayan Mishra, Lakshmi; Khatri, Kejal; Mishra, Vishnu Narayan (JOURNAL OF ADVANCES IN PHYSICS, 2023)
This paper aims to describe the application of educational tools with which it can develop interactivity and help pupils and students to better and more clearly understand mathematics and to understand that it is all around us, that it is our everyday life. The paper will show the ways of creating mathematical educational materials and their use. The calculation of partial differential equations has a wide application. Many problems in scientific research and engineering can be mathematically modeled by partial differential equations. A differential equation containing multiple independent variables is called a PDE (partial differential equation).